Range dynamics in sibling species: facts and reconstructions for the mammal fauna of Eastern Europe - Zagorodniuk, I. (Theriologia Ukrainica, 2019)
The specifics of distribution and status of local mammal species of sibling complexes demonstrating signs of significant either current or recent range dynamics are considered. These species complexes comprise pairs of sibling and morphologically close species, which until recently have not been unambiguously distinguished, thus it was impossible to analyse their range dynamics. However, range dynamics of this group of species is of great interest since it determines the emergence of high species diversity and realisation of mechanisms of compact organisation of communities that include close species. The amassed by today knowledge on distribution of species and the identification criteria developed for some of those species based on collection specimens allow to analyse changes in their distribution ranges. Such data in most cases allow to perform reconstructions and to develop respective hypotheses on dispersal routes of species in the region. In total, 9 species complexes were considered. Ranges of species that by direct or indirect evidence demonstrate changes in the area of their distribution and in the same time change the system of interspecific spatial relationships within each group are described. These spatial relationships can vary from allopatry to marginal or significant sympatry. Such complexes of “small” species were described in the composition of former “large” polytypic species with signs of invasions or expansions of their components among bats (Plecotus auritus + austriacus, Pipistrellus pipistrellus + pygmaeus, Eptesicus serotinus + lobatus) and rodents (Spermophilus suslicus + odessanus, Microtus arvalis + obscurus, Mus musculus + spicilegus). Similar but less expressed signs can be also traced in some other groups (Spalax zemni + arenarius, Sylvaemus sylvaticus + whiterbyi, Capreolus capreolus + pygargus). Distribution maps for all these species complexes are presented with reconstructions of possible directions of their dispersal through the territory of the region (Ukraine and adjacent countries). Zones of prochoresis, where these species most likely were absent in the recent past, are determined and analysed. The time and pace of expansion of “small” species in the region are estimated. The significance of morphological criteria of species and the possibilities of revision of old collection specimens to analyse temporal changes of biota are shown as well as the importance of cartographic data for such analysis. By using data from revisions, it is possible to estimate geographical tendencies and velocity of expansion for many species, including those that represent groups of morphologically close or sibling species. Розглянуто особливості поширення та статусу присутності у складі місцевої фауни видів ссавців, що входять до складу двійникових комплексів і демонструють ознаки суттєвих змін ареалів, як поточних, так і нещодавніх. Цей комплекс видів сформований парами видів-двійників та морфологічно близьких видів, яких до останнього часу не розрізняли або розрізняли з низкою застережень, а тому неможливо було аналізувати зміни їхніх ареалів. Попри це, саме зміни ареалів такої групи видів являють головний інтерес, оскільки визначають формування високого видового різноманіття біоти і реалізацію механізмів щільної упаковки угруповань, що включають близькі види. Накопичені на сьогодні відомості про поширення видів та розроблені критерії ідентифікації частини таких видів за давніми колекційними зразками дозволяють аналізувати зміни їхніх ареалів. У значній частині випадків такі дані дозволяють проводити реконструкції та формулювати відповідні гіпотези щодо шляхів розселення видів в регіоні. Загалом розглянуто 9 видових комплексів, в кожному з яких виокремлено та описано ареали тих видів, які за прямими або непрямими даними демонструють динаміку меж свого поширення і тим самим змінюють систему просторових взаємин видів у групі, переважно від стану алопатрії до маргінальної або суттєвої симпатрії. Такі комплекси «малих» видів зі складу колишніх «великих» політипних видів з виразними ознаками інвазій та експансій їх складових виявлено серед кажанів (Plecotus auritus + austriacus, Pipistrellus pipistrellus + pygmaeus, Eptesicus serotinus + lobatus), п’яти надвидів гризунів (Spermophilus suslicus + odessanus, Microtus arvalis + obscurus, Mus musculus + spicilegus). Подібні менш виразні ознаки є й у інших групах (Spalax zemni + arenarius, Sylvaemus sylvaticus + whiterbyi, Capreolus capreolus + pygargus). Для всіх цих груп представлено карти поширення з реконструкціями напрямків їхнього ймовірного розселення по території регіону (територія України та суміжних країн) з визначенням та аналізом зон прохорезу, де ці види найімовірніше були відсутні в недавньому минулому. Зроблено оцінки часу і темпів експансії «малих» видів в регіоні. Показано значення морфологічних критеріїв видів та можливостей перевизначення старих колекційних зразків для аналізу вікових змін біоти, а також значення картографічних даних для такого аналізу. Використовуючи перевизначення даних, можна оцінити географічні тенденції та швидкість розширення для багатьох видів, включаючи представників груп з морфологічно близькими та рідними видами.